Tratamento de efluentes de carcinicultura por macrófitas aquáticas flutuantes - Henry-Silva, Gustavo Gonzaga [UNESP]; Camargo, Antonio Fernando Monteiro [UNESP] (FapUNIFESP (SciELO), 2008)
The efficiency of systems composed of two species of floating aquatic macrophyte (Eichhornia crassipes and Pistia stratiotes) to treat effluents from shrimp culture was evaluated in this research. The effluent originated from a pond populated with Macrobrachium amazonicum. Treatment systems consisted of 12 experimental tanks with aquatic macrophyte and three tanks without plants (control). Water samples were collected from the fresh water supply and before and after passing through the treatment systems. There are no differences in the removal of nutrients between the two species. The higher nutrient removal was observed for total phosphorus (41.9% by control; 71.6% by E. crassipes; 69.9 by P. stratiotes; 72.5% by E. crassipes + P. stratiotes and 72.1 by P. stratiotes + E. crassipes) and turbidity (30.6% by control; 80.2% by E. crassipes; 75.2 by P. stratiotes; 79.8% by E. crassipes + P. stratiotes and 81.5 by P. stratiotes + E. crassipes). The systems containing aquatic macrophytes were efficient in nitrogen and phosphorus removal from M. amazonicum culture. © 2008 Sociedade Brasileira de Zootecnia.
Treatment of shrimp effluents by free-floating aquatic macrophytes
Keywords: Aquaculture; Eichhornia crassipes; Macrobrachium amazonicum; Nutrients; Pistia stratiotes; Decapoda (Crustacea); Eichhornia